Social solutions for the digital divide: The case of emergency aid during the covid-19 pandemic - Prado de Morais Giglio, Giuliano; Alves da Silva, Valéria; Alves da Silva, Renata (Guará Journal, 2024)
The COVID-19 pandemic led to social isolation, forcing people to access information and personal contacts primarily through the internet, using digital remote access tools, various websites, and, above all, mobile apps. This became even more evident with the Federal Government's Emergency Aid program, which was entirely digital. In this case, the majority of the target population was socially vulnerable and lacked basic computer skills, requiring immediate access to digital media to avoid jeopardizing their rights. This project was designed to offer specialized IT support to meet these individuals' digital needs, enabling them to integrate into the digital process imposed by the pandemic, especially the Emergency Aid process. This support program involved more than 60 volunteers, including students and faculty from UFES Alegre campus, as well as civil society and its institutions, providing daily, specialized support to more than 700 people. In addition to the emergency aid process, it enabled hundreds of people to adapt their documents, access web services, and access to justice and civil rights amid the crisis of in-person institution closures.
Keywords: Digital inclusion; Pandemic; Emergency aid; Social action